Development of Website-Based Multimedia “Project Three” on Body Painting Learning Achievements - Muhammad Rizal Agus Adriansyah; Hadromi; Ahmad Roziqin; Sonika Maulana (JMEL : Journal of Mechanical Engineering Learning, 2025)
This study aimed to develop a website-based multimedia product, Project Three, for body painting learning and to examine its feasibility, effectiveness, and student responses in vocational automotive education. The research used a research and development design with the ADDIE model, covering analysis, design, development, implementation, and evaluation stages. The product was implemented in the Light Vehicle Body Engineering Department of SMKN 5 Kendal using a one-group pretest–posttest design involving 23 grade XI students. Data were collected through expert validation sheets, learning achievement tests, reliability testing, normality testing, non-parametric statistical testing, N-gain analysis, and student response questionnaires. The developed multimedia obtained very feasible validation scores from media experts at 93.60% and material experts at 97.05%. The test instrument showed excellent reliability, with a Cronbach’s Alpha value of 0.984 for 35 items. The normality test indicated non-normal data distribution, while the statistical test showed a significant difference between pretest and posttest scores. The N-gain mean was 0.6716, categorized as moderate, with an effectiveness percentage of 67.16%, indicating that the product was quite effective. Student responses reached 84.09%, categorized as appropriate. Project Three is feasible and moderately effective for supporting body painting learning outcomes in vocational high school settings.